Preparation and properties of benzocyclobutene based low-k linear polysiloxane. Issue 23 (1st June 2022) - Peng, Qiuxia; Hu, Huan; Deng, Yueting; Long, Quan; Ma, Jiajun; Yang, Junxiao
Abstract : Linear BCB-containing polysiloxane with low k, low CTE, high T 5 and high transparency was synthesized through Heck reaction and hydrolysis condensation reaction. Abstract : Most benzocyclobutene (BCB) resins require a thermal pre-polymerization process to achieve the desired viscosity for application. However, the process is difficult to control because it is time-consuming and requires high temperatures. Therefore, a mild and simple method for preparing BCB based polysiloxane is proposed herein. Using a combination of the Heck reaction and hydrolytic condensation, linear BCB-based polysiloxane of various molecular weights can be routinely prepared by controlling the hydrolysis conditions. The obtained polymers have excellent dielectric properties (dielectric constants < 2.5 at 10 MHz) and thermal stability ( T 5 (the temperature of 5% weight loss) > 470 °C) after curing.